Curcuma longa L. helps macrophages to control opportunistic micro-organisms during host-microbe interactions - W Figueira, Leandro [UNESP]; De Oliveira, Jonatas R. [UNESP]; Netto, Amandio A.L.; S Zamarioli, Lucas Dos; Marcucci, Maria C.; Camargo, Samira E.A.; De Oliveira, Luciane D. [UNESP] (Taylor & Francis, 2020)
Aim: Plant products have been evaluated to control opportunistic micro-organisms, as well as fortify immune system cells. Thus, Curcuma longa L. (turmeric) extract was evaluated in interactions of murine macrophages (RAW 264.7) with Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans, in order to establish cooperation with defense cells. Materials & methods: Effects of minimal inhibitory concentrations (MIC) of the plant extract were analyzed on phagocytosis, cell viability of RAW 264.7 and production of inflammation-related molecules (IL-1β, TNF-α, IL-10 and NO). Results: The plant extract was cytocompatible and promoted significant reductions of micro-organisms, and synthesis of inflammation-related molecules, during interactions. Conclusion: C. longa L. extract showed significant antimicrobial response and cooperation with macrophages, by fighting bacteria and yeasts during host-microbe interactions.
Keywords: Candida albicans; Curcuma longa L.; host-microbe interaction; macrophages; Pseudomonas aeruginosa; RAW 264.7; Staphylococcus aureus